PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV. PERKASA MOTOR DI KOTA JAYAPURA - Heber Moyau; Munawir Lobubun; Fitriani (ark:/00000/jeb.v12i1, 2021)
The purpose of this study was to determine and analyze the effect of the work environment on the performance of employees of CV. Perkasa Motor in Jayapura City. This research is a quantitative research using simple linear regression statistical analysis method. Data analysis in this study used descriptive analysis and simple linear regression analysis (t test, correlation coefficient and coefficient of determination) assisted by the SPSS 22 for windows program. Based on descriptive analysis shows that the majority of respondents agree with the work environment in CV. Perkasa Motor is good so that performance increases, while the statistical tests that have been described can be seen that the work environment variable affects employee performance variables and it can be seen that the work environment affects employee performance CV. Perkasa Motor in Jayapura City, so that the first hypothesis that the work environment has a positive and significant effect is accepted, while the second hypothesis states that the work environment has no effect on employee performance which is rejected, meaning that the work environment has a positive and significant effect on employee performance CV. Perkasa Motor in Jayapura City. In addition, the coefficient of determination shows that there is an influence of the work environment on the performance of CV employees. Perkasa Motor in Jayapura City by 53.9%, while the rest is influenced by other variables or factors not examined. Keywords: Work Environment, Employee Performance